Effectiveness of Snakehead Fish (Channa striata) and Turmeric (Curcuma domestica) Extract towards Wound Healing in Rats (Rattus norvegicus) - Widyawati, Ratna (Faculty of Veterinary Medicine Universitas Brawijaya, 2020)
This study aimed to determine the effect of snakehead fish extracts (Channa striata) and turmeric extract (Curcuma domestica) towards incision wound healing in rats (Rattus norvegicus). Twenty-four male rats, aged 8-week-old, 200-300 grams of body weight divided into 4 groups: control (P0), treatment with povidone iodine as positive control (P1), treatment with snakehead fish extract (P2) and treatment with turmeric extract (P3). The rats were given premedication consisting of acepromazine 0.5 mg kg / BW and atropine 10 mg / kg BW. The rats were then anesthetized using ketamine 0.1 mg / kg BW. An incision was made on each rats’ back area along 2 cm with 0.05 mm depth and observed for 14 days. Observations were carried out every day with data collection at <7 days, 7-14 days, and 14 days. The One-Way ANOVA statistical analysis resulted that the wound fluid parameters and the duration of wound healing showed no significant difference between P0, P1, P2 and P3. This study concluded that the administration of povidone iodine, snakehead fish extract, and turmeric extract influenced the healing of incision wounds in rats.